The botanical biofiltration of volatile organic compounds and particulate matter derived from cigarette smoke. (May 2022) - Morgan, Angela L.; Torpy, Fraser R.; Irga, Peter J.; Fleck, Robert; Gill, Raissa L.; Pettit, Thomas
Abstract: Despite the growing use of control measures, environmental tobacco smoke (ETS) remains a significant pollutant source in indoor air in many areas of the world. Current control methods for reducing ETS exposure are inadequate to protect public health in environments where cigarettes are smoked. An alternative solution is botanical biofiltration which has previously been shown to lower concentrations of volatile organic compounds (VOCs) and particulate matter (PM) from a range of polluted air streams. This study is the first to assess the potential of a botanical biofilter with the species Spathiphyllum wallisii (Peace Lily) for the removal of cigarette-derived VOCs and all size fractions of PM. Single pass removal efficiencies of 43.26% for total VOCs and 34.37% for total suspended particles were achieved. The botanical biofilter reduced the concentrations of a range of harmful ETS chemicals including nicotine, limonene, and toluene. Evaluation of the re-emission of ETS constituents filtered by the botanical biofilter revealed no particle resuspension or off gassing. The results demonstrate the potential of botanical biofilters to reduce public ETS exposure, although further research is needed to improve upon and ensure the efficiency of these systems for practical applications. Graphical abstract: Image 1 Highlights: Active green walls filter a proportion of cigarette smoke. Total volatile organic compound single pass removal efficiency was 43.26%. Removal efficiency depends on type of volatile organic compound. Total suspended particle single pass removal efficiency was 34.37%. There was no post-filtration re-emission or re-suspension of cigarette smoke.